Promoción y turismo gastronómico en la Ciudad de Riobamba, Provincia de Chimborazo. - Rojas Andrade, Erick Marcelo (2022)
This project aims for people to understand the current situation of gastronomic tourism in Riobamba and the current condition of its promotion because it is a contribution that contributes to the economy of the city. Therefore, it is necessary to pay attention to the current reality as tourism activities, reflect its profitability for the urban economy, and a truthful approach in the current post-covid scenario. On the subject of gastronomy, having a discreet promotion on the offer of its typical dishes makes the tourist find himself in a clear position of absolute confusion. So it is necessary to improve the diffusion of what is offered to the tourist and identify the places that stand out for their better service and proposal. The current image of gastronomic tourism is very little valued at the provincial and national levels. It reflects its deficiency in economic profitability due to a defective promotion, generating little income, which is related to the current problematic situation that Ecuadorians are going through, which pushes towards an inaccurate or unknown position of workers in the area of traditional food and beverages. Considering all of the facts, it is necessary to collect data that shows the true state of Riobambeño's traditional gastronomy and its direct and indirect contribution to the city's tourism, explaining which are the advantages that the establishments have and how it works its promotion to find the best strategies that help to solve the current precarious situation.